Password managers: a critical review of security, usability, and innovative designs - Alsharaya, Hussein (Journal of Computer Sciences Institute, 2025)
Password managers are crucial for securely managing online credentials in today’s digital landscape. This review synthesizes insights from 25 research papers to evaluate current password management systems, focusing on their approaches to security, usability, and innovation. We explore strategies to counter security challenges such as offline attacks, phishing, and device compromise, as well as efforts to enhance usability through intuitive interfaces and simplified authentication. The review also analyzes innovative architectural designs and cryptographic techniques that underpin these systems. Our synthesis highlights significant advancements in creating secure, resilient, and user-friendly password managers, while identifying gaps in usability testing, scalability of distributed systems, and cryptographic standardization. This comprehensive overview provides critical insights and directions for future research to optimize the balance between security and usability in password management.